(untitled) (Development Service Industry Management, 2025)
Ensuring the economic security of an enterprise as a process represents a relatively new type of enterprise activity ‑ security-providing, the management of which is based on taking into account, first of all, the specific features of the economic activities of the enterprise. The article discusses the characteristic features of the construction industry, the specifics of construction products that are a direct, useful result of the production activities of construction enterprises, and the peculiarities of the activities of construction enterprises (large volume and significant variety of construction works, diversity of types and objects of construction, long duration of the construction process, etc.). The distinguishing feature of construction companies is their performance of various functions, which determine their legal status in the creation of construction products, somewhat enshrined in the current legislation of Ukraine (customer, developer, contractor, investor). The status of a business entity in construction determines all aspects of its activities ‑ from funding construction works at the site to the extent and type of responsibility for the results of the activities and accordingly affects approaches to ensuring economic security. The distinct feature of construction companies’ activities is the multitude of sources of funding for a project, which is determined by its purpose (industrial facility, social infrastructure object, or residential building), the legal status of the construction company, and the necessity of attracting loan (debt) financing, which is a source of risks to the construction companies’ operations. In the activities of construction companies, there are problematic situations and tasks that arise due to global and local challenges and require quick resolution as soon as possible. Problematic situations and tasks share a common feature ‑ the likelihood of transforming into specific threats to the activities of construction companies, which is high due to a number of conditions and circumstances, particularly the lack of necessary attention from owners and managers of construction companies to addressing problematic situations and tasks.